Three-dimensional crystal plasticity simulations using peridynamics theory and experimental comparison. (July 2021) - Lakshmanan, Aaditya; Luo, Jiangyi; Javaheri, Iman; Sundararaghavan, Veera
Abstract: A three-dimensional (3D) peridynamics (PD) model of crystal plasticity (CP) is presented for predicting the fine-scale localization in polycrystalline microstructures undergoing elastoplastic deformation. Microscale data from electron microscopy and digital image correlation have indicated that slip localizations arise early in deformation and act as precursors to mechanical failure and fracture. However, classical numerical approaches such as crystal plasticity finite element methods (CPFEM) are generally unable to predict the emergence and distribution of such localizations. Alternatively, the PD formulation has attracted significant attention for its unique treatment of deformation in the presence of high strain gradient fields. In this paper, a mesh-free non-ordinary state-based PD technique is developed for simulating the elasto-plastic deformation of 3D polycrystalline aggregates of a magnesium alloy. This work presents the details of 3D polycrystal plasticity modeling using PD theory with experimental and CPFEM comparisons. The results from this model are validated against published experimental data for the stress-strain response and texture evolution. The crystal plasticity peridynamic (CPPD) models are successful in simulating grain averaged strains seen in the experiment and depict well-resolved regions of strain localization.